PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS ICT (INFORMATION,COMMUNICATION, AND TECHNOLOGY) TERHADAP MOTIVASI BELAJAR SISWAKELAS X PADA PEMBELAJARAN EKONOMI DI SMAN 1 BANGUNTAPAN - Miftakhul Hidayah, Sri Nuryanto, dan Miftahul Fawaid (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This research aimed to discover how much influence the use of ICT‐based Learning Media onstudent motivation in learning economics class X in SMA N 1 Banguntapan. The research methodused in this study is the experimental method.While the research design that was used is